Bingkai Republika Online dan Kompas.com Atas Kasus Rizieq Shihab Selama Mei – Juni 2017 - Pratama, Sapria (Jurnal Review Politik, 2017)
The leaking of a pornographic content conversation transcript via the Whatsapp conversation application that involves the high priest of the Islamic Defenders Front (FPI) and Firza Husein invites the public debate and furore in the mass media, including online media Kompas.com and Republika.co.id. The case became more and more crowded discussed after Rizieq Shihab known to leave Indonesia and never returned to meet the call examination by the authorities. A number of parties considered the move as an attempt to escape legal responsibility. But Rizieq Shihab party declared it as a form of resistance to the criminalization of the ulama. Until his status was raised as a suspect, the alleged criminalization of the clergy in the case is still being voiced, especially by Rizieq Shihab sympathizers. In this study, researchers found results if the framing of news on online media Kompas.com has put forward the image of Rizieq as a suspect before the verdict was enforced by the police. Kompas.com consistently denied and asserted, there is no criminalization in the case of Rizieq Shihab's law. Similarly, the online media Republika.co.id. Framing the news in the media also denied any attempt to criminalize the clergy in the case of Rizieq Shihab. However, before the verdict of the suspect is given, Republika.co.id still consider other possibilities such as the existence of engineering in the case.